Using Planar Laser Induced Fluorescence to explore the mechanism of the explosive disintegration of water emulsion droplets exposed to intense heating; International Journal of Thermal Sciences; Vol. 127 - Volkov R. S. Roman Sergeevich (2018, 2018)
Title screen